Nurses' Experiences of Documenting the Mental Health of Older Patients in Long-Term Care - Eli Johanne Haugan Engen; Siri Andreassen Devik; Rose Mari Olsen (SAGE Publishing, 2020)
Nursing documentation is repeatedly reported to be insufficient and unsatisfactory. Although nurses should apply a holistic approach, they tend to document physical needs more often than other caring dimensions. This study aimed to describe nurses' experiences documenting mental health in older patients receiving long-term care. Individual interviews were conducted with nine nurses and were analyzed by content analysis. One main theme, two categories and seven sub-categories emerged. The findings showed that the nurses perceived mental health as an ambiguous phenomenon that could be difficult to observe, interpret, and agree upon. Thus, the nurses were uncertain about what concepts and words corresponded to their observations. They also struggled with finding the right words to create accurate and complete documentation without breaking confidentiality or diminishing the dignity of the patient. The findings are relevant for nurses in different types of healthcare services and in the educational context to ensure comprehensive nursing documentation.